BERYLLIUM IN SILICIC MAGMAS AND THE ORIGIN OF BERYL-BEARING PEGMATITES - London D.; Evensen J.M. (My University, 2002)
This chapter addresses the portion of the geochemical cycle of beryllium that entails its transfer through the continental crust by the generation and migration of silicic magmas, which will be referred to loosely as granitic but will include all of the textural variants of rocks derived from the granitic bulk compositions. Within the granite system, we will examine the distribution of Be between anatectic melts and residual crystals, and we will track the accumulation of Be in melt via crystal fractionation, culminating in the saturation of pegmatite-forming melts in the mineral beryl. Beryl is unquestionably the most common manifestation of Be enrichment, and the most abundant of the phases that contain essential beryllium (see Cerný this volume). To explain the presence of beryl in pegmatites, we pose four questions: 1. How much Be does it take to saturate a granitic (pegmatite-forming) melt in beryl? 2. How much Be is likely to be incorporated in silicic partial melts at their source? 3. Consequently, how much fractionation of a typical granitic magma must occur to achieve beryl saturation in pegmatitic derivatives (or is beryl saturation possible without extended magmatic fractionation)? 4. And should all granitic magmas be expected to achieve beryl saturation eventually, or are there special attributes of the source material or crystalline phases in the magma that predetermine the likelihood of forming beryl in pegmatitic differentiates? To address these questions, we start with a review of beryl saturation in pegmatites. We then examine the likely abundance of Be derived by anatexis at the sources of granitic magmas. With the two ends of the system bracketed, we can then subject Be fractionation to conventional modeling methods to ascertain how much fractionation must take place to bring granitic melts to beryl saturation. As a review, this chapter relies as much as possible on readily available publications …